Title: a title should be provided concisely (10-12 words) (Garamond font style, 16 pt, Sentence case, justify) - Last Name, First Name (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2012)
Maximum of 200 words, the abstract should consist at least; short background (voluntary), Purpose (mandatory), Design/methodology/approach (mandatory), Main findings (mandatory), Practical implications (if applicable), and Conclusions. Abstract should be constructed in a single paragraph and exclusive of any literature review. Please provide minimum five and up to seven keywords which encapsulate the principal topics of the paper.Keywords:AaaaaBbbbbCccccDdddd